Association of 3q21q26 syndrome with different RPN1/EVI1 fusion transcripts - G Martinelli; E Ottaviani; S Buonamici; A Isidori; G Borsaru; G Visani; PP Piccaluga; M Malagola; N Testoni; M Rondoni; G Nucifora; S Tura; et al. (Haematologica, 2003)
BACKGROUND AND OBJECTIVES: Patients with acute myeloblastic leukemia (AML) with features of myelodysplastic syndrome and abnormalities of megakaryocytopoiesis often have cytogenetic aberrations of 3q21 and 3q26 bands involving the paracentric inversion [inv(3) (q21q26)] or a reciprocal translocation [t(3;3) (q21;q26)]. These abnormalities frequently cause inappropriate expression of the EVI1 gene located at 3q26. Other genes that have been implicated at the rearrangement breakpoint are GR6 and RPN1 (both on 3q21). The aim of this study was to investigate the expression of the EVI1 fusion genes in AML patients with 3q21q26 syndrome. DESIGN AND METHODS: We used reverse transcription polymerase chain reaction to evaluate the expression of EVI1 and GR6, and particularly of the fusion genes RPN1-EVI1 and GR6-EVI1 in 9 AML patients with either inv(3)(q21q26) (7 cases) or t(3;3)(q21;q26) (2 cases). RESULTS: EVI1 and GR6 were always expressed, as was RPN1-EVI1; GR6-EVI1 was absent. In 8/9 patients, the part of EVI1 retained in RPN1-DEVI1 contained blocks B and C of the PR domain commonly found in the MDS1-EVI1 gene. In the remaining patient [with inv(3) (q21q26)], only block C was retained: we named this variant fusion gene RPN1-DEVI1. This patient lacked the micromegakaryocytopoiesis frequently found in 3q21q26 syndrome. INTERPRETATION AND CONCLUSIONS: These findings support the hypothesis that EVI1 activation plays a dominant role in the pathogenesis of the 3q21q26 syndrome. EVI1 expression might occur either as a consequence of rearrangements leading to the formation of different fusion transcripts, such as RPN1-EVI1 and RPN1-DEVI1 or following disruption of the PR activation domain of the MDS1-EVI1 gene.